Shakespeare in the cinema : ocular proof - Buhler, Stephen M., 1954- (State University of New York Press, 2002)
A comprehensive look at strategies that filmmakers have employed in adapting Shakespeare's plays to the cinema, this book investigates what the task of adaptation reveals about film in general and focuses on patterns and approaches shared by various cinematic works. It spans more than a century of film, beginning with an 1899 version of King John.
Keywords: Shakespeare, William, -- 1564-1616 -- Film adaptations.; Shakespeare, William, -- 1564-1616; Shakespeare, William -- 1564-1616; Bibel -- Philemonbrief; Shakespeare, William.; English drama -- Film adaptations.; Film adaptations -- History and criticism.; Théâtre anglais -- Adaptations cinématographiques.; Adaptations cinématographiques -- Histoire et critique.; PERFORMING ARTS -- Film & Video -- Reference.; English drama; Film adaptations; Geschichte; Drama; Film; Criticism, interpretation, etc.; Film adaptations.; Adaptations cinématographiques.